SIRT1 and miR-34a-5p Expression in PBMCs as Potential Biomarkers for Patients With Type 2 Diabetes With Cognitive Impairments - Liu, Xiaofeng; Zhao, Zhipei; Chen, Dengbin; Zhang, Zeqin; Lin, Xiaozhen; Shen, Zhanbo; Lin, Qingwen; Fan, Kengna; Wang, Qi; Zhang, Weiqing; Ou, Qishui (The journal of clinical endocrinology and metabolism, 2024)
Abstract Context Patients with type 2 diabetes mellitus (T2DM) are at significantly increased risk of Alzheimer disease (AD). However, no biomarkers are available for early identification of patients with T2DM with cognitive impairment (T2DM-CI). Mitochondrial dysfunction is linked to AD. Silent Information Regulator 1 (SIRT1), which is responsible for regulating mitochondrial biogenesis, and its related miRNAs were also altered in AD. Objective This study aimed to determine whether mitochondrial function in peripheral blood mononuclear cells (PBMCs) of patients with T2DM-CI was altered and if these alterations could be used as biomarkers. Methods A total of 374 subjects were enrolled, including AD, T2DM-CI, T2DM-nCI (T2DM without cognitive impairment), and healthy controls. The mitochondrial function was determined using a commercial assay kit. The mitochondrial DNA (mtDNA) content, the expression of SIRT1, and selected miRNAs in PBMCs were measured by quantitative polymerase chain reaction. The correlations and diagnostic accuracy were assessed using the Spearman correlation coefficient or receiver operating characteristics analysis, respectively. Results We found significant changes in mitochondrial function in PBMCs of patients with AD compared with controls (all P < .05), which were not found in T2DM-CI. However, mtDNA content and SIRT1 mRNA expression were lower in PBMCs of patients with T2DM-CI, while miR-34a-5p expression was higher than in patients with T2DM-nCI (all P < .05). A combination of SIRT1 and miR-34a-5p demonstrated excellent discrimination between T2DM-CI and T2DM-nCI (area under the curve = 0.793; sensitivity: 80.01%; specificity: 78.46%). Furthermore, correlation analysis revealed a link between miR-34a-5p expression and hyperglycemia in T2DM-CI. Conclusion Our findings revealed that there was an alteration of mitochondria at the peripheral level in patients with T2DM-CI. SIRT1 combined with miR-34a-5p in PBMCs performed well in identifying patients with T2DM-CI and may be a promising biomarker.